Prognostic markers of inflammation in endometrioid and clear cell ovarian cancer. Issue 8 (18th April 2022) - Gallego, Alejandro; Mendiola, Marta; Hernando, Barbara; Berjon, Alberto; Cadiz, Alice; Chaves-Urbano, Blas; Heredia-Soto, Victoria; Spagnolo, Emanuela; Hernández Gutiérrez, Alicia; Hardisson, David; Macintyre, Geoff; Redondo, Andres; et al.
Abstract : Objectives: Cancer-related systemic inflammation has been associated with prognosis in multiple cancer types. Conversely, local inflammation, which is characterized by dense intratumoral immune infiltrates, is a favorable predictor of survival outcome. However, these survival associations are not well established in ovarian cancer, particularly in the less frequent endometrioid and clear cell endometriosis associated histotypes. Methods: This retrospective study included 119 patients (63 endometrioid and 56 clear cell ovarian carcinomas). We performed a comprehensive survival association analysis of both systemic (neutrophil-to-lymphocyte ratio or presence of endometriosis) and local inflammation markers (CD3+ and CD8+ tumor infiltrating lymphocytes) using multivariate Cox proportional hazards models that account for confounding factors. Results: Medium to high levels of intraepithelial CD8+ tumor infiltrating lymphocytes are associated with longer survival in endometrioid ovarian cancer (p=0.04). In addition, we found that intraepithelial CD8+ tumor infiltrating lymphocytes are prognostic in clear cell ovarian cancer (p=0.02), and that intraepithelial CD3+ tumor infiltrating lymphocytes are also associated with improved outcome (p=0.02). Furthermore, intratumoral CD3+ and CD8+ tumor infiltrating lymphocytes showed improved prognosis in the endometrioid subtype (p<0.1). No prognostic value was observed for systemic immune markers. Conclusions: In this study, patients with endometrioid and clear cell ovarian cancer with moderate to high CD8+ and CD3+ intraepithelial tumor infiltrating lymphocytes had longer overall survival. Higher expression of intratumoral CD3+ and CD8+ tumor infiltrating lymphocytes also showed an improved outcome in endometrioid ovarian cancer. In contrast, systemic inflammation, evaluated by neutrophil-to-lymphocyte ratio or presence of endometriosis, did not have a prognostic impact in these histologic subtypes.